Dostosowanie wymagań edukacyjnych do możliwości uczniów ze specjalnymi potrzebami na lekcjach języka angielskiego a test ósmoklasisty - Paluch, Magdalena (Neofilolog, 2022)
The last decade has seen rapid growth in the number of students with special educational needs (SEN). The aim of inclusive education is to provide all students with equal public education. To facilitate the learning process for students with SEN changes and modifications to requirements are implemented by language teachers. At the same time, these students take the final exam at the end of year eight of their primary education, where the main and almost only adjustment is extended time to write the exam. This article has two main aims. The first is to compare the legal requirements for educational adaptations in the Polish education system. The second is to show, on the basis of a case study, that lack of coherence between the different regulations affects the results achieved by the students in their final exams.